Russia, arctic ship, S.Y. America, Franz Josef Land - Fiala, Anthony, 1869-1950 (1901)
"A Moonlight picture of the "America," of the first Ziegler Expedition, in the arctic." Caption taken from Fiala, A. (January, 1913). The Man in the Parka. Boys' Life. 2(11). 6-7. Retrieved from http://books.google.com/books?id=3JVqekZbzz8C&pg=PA6&lpg=PA6&dq=%22A+moonlight+picture%22++%22Fiala%22&source=bl&ots=ylVZksMSER&sig=bLX4_QAWDzURYYpZeQDHgW8sR9Y&hl=en&sa=X&ei=uH6CUanlJYrKqQHQzYHoCQ&ved=0CC0Q6AEwAA#v=onepage&q=%22A%20moonlight%20picture%22%20%20%22Fiala%22&f=false